218. A Phase 1 Study of the Single-Dose Safety, Tolerability, and Pharmacokinetics of the Beta-lactamase inhibitor Xeruborbactam Administered as the Isobutyryloxymethyl Oral Prodrug to Healthy Adult Subjects. (15th December 2022) - Griffith, David; Roberts, Jason; Wallis, Steven; Hernandez-Mitre, Maria Patricia; Morgan, Elizabeth; Dudley, Michael; Loutit, Jeff
Abstract: Background: Xeruborbactam (XERU) is a member of a new class of cyclic boronic acid β-lactamase inhibitors with inhibitory activity against major members of Class A, B, C, and D beta-lactamases. This report describes the first safety and pharmacokinetic data following oral administration as the isobutyryloxymethyl prodrug in humans. Methods: Forty-eight healthy subjects were enrolled into one of 6 cohorts of 8 subjects each in the single ascending doses (100, 200, 400, 600, 800, and 1000 mg). Subjects were randomly assigned with each cohort to XERU oral prodrug (n = 6), or placebo capsule (n = 2). Intensive plasma (total drug) and ultrafiltrate (free drug) sampling was obtained after dosing and assayed for QPX7831 and XERU content using validated HPLC/MS methods. Results: XERU PK parameters following oral administration as the prodrug are shown in the table below. Compared to IV XERU doses (data not shown), XERU bioavailability is 90 - 100% orally bioavailable. XERU PK Parameter XERU XERU XERU XERU XERU XERU 100 mg 200 mg 400 mg 600 mg 800 mg 1000 mg (N=5) (N=6) (N=6) (N=6) (N=6) (N=5) Cmax (mg/L) 9.3 ± 1.7 17.0 ± 1.9 37.8 ± 3.7 52.53 ± 2.8 62.0 ± 9.7 82.7 ± 5.0 Tmax (hr) 2.3 ± 0.7 2.4 ± 1.1 2.3 ± 0.8 3.7 ± 1.4 3.3 ± 0.8 3.4 ± 0.6 AUC0-inf (mg·h/L) 324.0 ± 65.9 507.0 ± 36.8 1157.5 ± 153.4 1371.5 ± 150.3 1838.1 ± 302.6 2332.2 ± 197.1 Free AUC0-inf (mg·h/L) 20.8 ± 5.6 32.4 ± 2.8 93.1 ± 13.4 107.3 ± 25.5 155.8 ± 24.2 204.5 ± 40.0 Free AUC0-24 (mg·h/L) 10.5 ± 3.4 18.8 ± 2.3 51.1 ± 5.4 68.1 ± 19.4 92.8 ± 15.3 115.6 ± 23.7 CL/F (L/h) 0.32 ± 0.06 0.40 ± 0.03 0.35 ± 0.05 0.44 ± 0.05 0.45 ± 0.07 0.43 ± 0.04 Vz/F (L) 15.4 ± 2.9 17.4 ± 1.3 15.0 ± 2.6 16.8 ± 3.0 17.61 ± 1.9 16.3 ± 1.3 Half-Life (h) 33.5 ± 2.1 30.5 ± 2.0 30.0 ± 5.3 26.4 ± 4.5 27.7 ± 2.4 26.4 ± 3.9 No subjects discontinued due to AEs and no SAEs were observed. There was no evidence of increasing numbers or severity of AEs with increasing dose. All AEs were mild in severity. Conclusion: Orally administered XERU was safe and well tolerated at all doses tested. Plasma XERU AUC and Cmax increased with increasing dose. XERU exposures (24h free AUC) exceed the predicted PK-PD parameter for stasis with once-daily doses of 400 mg or higher and exceed the PK-PD parameter for 1-log of bacterial killing once daily doses of 800 mg or higher. XERU, administered as an oral prodrug, has plasma PK properties that support once-daily administration. Disclosures: David Griffith, n/a, Qpex Biopharma: Employee Jason Roberts, BPharm(Hons), PhD, FSHP, FISAC, British Society of Chemotherapy: Grant/Research Support|Cipla: Honoraria|Gilead: Advisor/Consultant|MSD: Advisor/Consultant|MSD: Honoraria|Pfizer: Board Member|Pfizer: Honoraria|Qpex: Grant/Research Support|Sandoz: Board Member|Summit: Advisor/Consultant|Wolters Kluwer: Advisor/Consultant Elizabeth Morgan, n/a, Qpex Biopharma: Employee Michael Dudley, n/a, ArrePath: Board Member|Qpex Biopharma: Board Member|Qpex Biopharma: Employee Jeff Loutit, MBChB, Qpex Biopharma: Employee.